The impact of Emotion-focused training for emotion couching delivered as mobile app on self-compassion and self-criticism - Halamová, Júlia; Mihaľo, Jakub; Bakoš, Lukáš (Frontiers in Psychology, 2023)
Being self-compassionate is considered a beneficial emotion regulation strategy. Therefore, the acquisition of emotional skills can raise self-compassion levels and consequently reduce self-criticism. Hence, the goal of the current study was to develop a mobile app based on the empirically proven group version of Emotion-Focused Training for Emotional Coaching (EFT-EC; Halamová & Kanovský, 2019) and test its effectiveness in reducing self-criticism and raising self-compassion and self-protection. The sample consisted of 85 participants, of whom 22.4% were men and 77.6% were women. The mean age was 32.53 (SD = 14.51), ranging from 18 to 74 years. The participants filled out the following scales immediately before and after using the fourteen-day mobile app: The Forms of Self-Criticizing/Attacking & Self-Reassuring Scale (FSCRS; Gilbert et al., 2004), The Sussex-Oxford Compassion for the Self Scale (SOCS-S; Gu et al., 2020), and The Short-form Version of The Scale for interpersonal behaviour (s-SIB; Arrindell et al., 2002). Use of the 14-day EFT-EC mobile app significantly improved self-compassion and self-reassurance and significantly reduced self-criticism compared to pre- and post-measurements. The results are promising as self-criticism is a transdiagnostic phenomenon observed in various kinds of psychopathology and reducing it may prevent the emergence of psychopathologies. Moreover, the mobile app intervention can easily be accessed by a wide range of users, without requiring the services of a mental health professional, and thereby reduces the potential risk of shame or stigmatization.